Intravascular ultrasound for morphological assessment of napkin-ring sign detected on multidetector computed tomography. (1st June 2016) - Kato, Masaya; Dote, Keigo; Miura, Katsuya; Yamaguchi, Yuji; Miyauchi, Shunsuke; Higashihara, Tasuku; Kubo, Yumiko; Yamane, Aya; Nakano, Yoshinori; Kagawa, Eisuke; Nagai, Michiaki; Oda, Noboru; et al.
Abstract: Background: Although napkin-ring sign (NRS) plaques assessed by multidetector computed tomography (MDCT) is identified as a high-risk feature, the detailed morphological features are still unknown. The purpose of this study was to elucidate the morphological features of the MDCT-assessed NRS using intravascular ultrasound (IVUS). Methods: We evaluated 204 plaques in 193 patients with non-ST-elevation acute coronary syndrome who were diagnosed using 128-slice MDCT and were assessed using IVUS prior to coronary intervention. Morphology was compared between plaques with and without MDCT-assessed NRS. Severe IVUS-assessed attenuation was defined as an attenuation angle > 180°. Results: NRS was detected in 49 lesions. MDCT-assessed plaque attenuation was lower (p < 0.0001), and cross-sectional plaque areas at lesion sites, remodeling index, and the prevalence of positive remodeling were greater, in lesions with NRS (p < 0.005, p < 0.0001, and p < 0.0001, respectively). Furthermore, the IVUS-assessed remodeling index and prevalence of severe attenuation and speckled echo appearance were significantly greater in lesions with NRS (p < 0.01, p < 0.0001, and p < 0.0001, respectively). Using multivariate analysis, IVUS-assessed speckled echo appearance was identified as an independent predictor of MDCT-assessed NRS (odds ratio, 3.59; 95% confidence interval, 1.49–8.66; p < 0.005). Conclusion: MDCT assessment of NRS may be associated with larger heterogeneous necrotic cores and greater positive remodeling.